Attitudes about EU expansion and zero‐sum thinking: Ireland from 2002 to 2009 as an important test. Issue 3 (28th May 2016) - Jackson, John E.; Mach, Bogdan W.; Miller‐Gonzalez, Jennifer L.
Abstract : EU expansion can be seen as a positive‐sum process benefiting all countries by creating larger markets that stimulate more productive economies through increased specialization and economies of scale, implying that the general public in all countries should favour expansion. Contrarily, expansion can be perceived as zero‐sum. Capital and production relocate from higher to lower wage regions while labour does the opposite, possibly raising unemployment and reducing wages in the higher wage regions. The general public in these countries may come to oppose EU expansion attributing any deterioration in their work situation to the gains of new citizens of the European Union. Analysis of changes in Irish attitudes towards EU expansion in 2002, 2007 and 2009 finds no evidence of a link from lowered economic conditions to increased opposition to EU expansion. The only evidence for zero‐sum thinking is that diminished economic circumstances are associated with increased opposition to immigration, but this is not associated with increased opposition to further EU expansion.